1983
DOI: 10.1128/jb.153.1.458-464.1983
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of the synthesis of D-ribulose 1,5-bisphosphate carboxylase/oxygenase from Rhodospirillum rubrum

Abstract: The synthesis of ribulose 1,5-bisphosphate carboxylase/oxygenase in Rhodospirillum rubrum was greatly influenced by the conditions of culture. When grown photolithotrophically in an atmosphere containing low levels of CO2 (1.5 to 2%), enzyme synthesis was derepressed, with the result that the enzyme comprised up to 50%6 of the soluble protein of the cells as determined by immunological quantitation. This response was not observed when R. rubrum was grown photolithotrophically in an atmosphere of 5% CO2 in hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…1). R. rubrum compensates for the low affinity of its form II RubisCO by massively overexpressing this enzyme, to 50% of total soluble protein, when grown autotrophically under low-CO 2 conditions (Sarles and Tabita 1983). The amount of RubisCO detected here suggests that the symbionts have a high concentration of intracellular CO 2 .…”
Section: Discussionmentioning
confidence: 65%
“…1). R. rubrum compensates for the low affinity of its form II RubisCO by massively overexpressing this enzyme, to 50% of total soluble protein, when grown autotrophically under low-CO 2 conditions (Sarles and Tabita 1983). The amount of RubisCO detected here suggests that the symbionts have a high concentration of intracellular CO 2 .…”
Section: Discussionmentioning
confidence: 65%
“…It has been previously shown that members of the Rhodospirillaceae derepress RuBP carboxylase/oxygenase synthesis to high levels during the stationary phase when grown with butyrate as the electron donor (15,17). This appears to be due, at least in part, -to the depletion of carbon dioxide from the medium (14). In addition, when wild-type R. sphaeroides was grown on malate and transferred, after extensive washing, to a medium containing no exogenous carbon, RuBP carboxylase/oxygenase levels were increased substantially.…”
Section: Resultsmentioning
confidence: 99%
“…Growth of R. rubrum in the butyrate-containing medium used in the present studies induces the biosynthesis of rubisco (34,40). The present research establishes that the poly(A)+ RNA species contain mRNA corresponding to this enzyme.…”
Section: Discussionmentioning
confidence: 88%
“…In Rhodospirillum rubrum grown in the light on butyrate-bicarbonate medium this enzyme comprises ca. 7% of the soluble protein (40), and maximal levels of rubisco are found after 5 to 6 days of growth under these conditions (34,39). In this communication, we MATERIALS AND METHODS Chemicals.…”
mentioning
confidence: 99%